Analysis of the differences between HPV-independent and HPV-related cervical adenocarcinoma - He, Jing; Tu lu Weng Jiang, Gulixian; Zeng, Lin (Frontiers in Oncology, 2025)
BackgroundNo prognostic evaluation criteria have been established for either human papillomavirus (HPV)-related cervical adenocarcinoma (HPV-CA) or HPV-independent cervical adenocarcinoma (HPV-Ind-CA). We aimed to compare and analyze the clinicopathological features and survival prognosis of patients with HPV-related and HPV-independent cervical adenocarcinoma to facilitate clinical diagnosis, treatment and survival prognosis of patients with cervical adenocarcinoma.MethodsClinical data were collected from 47 patients with HPV-Ind-CA (HPV-Ind-CA group) and 285 patients with HPV-CA (HPV-CA group), who were diagnosed at the Oncology Hospital affiliated with Xinjiang Medical University between October 2012 and July 2023. A retrospective analysis was performed to compare the clinical characteristics (including age, ethnicity, fundamental diseases, initial symptoms, gynecological examination findings such as contact bleeding, menstrual history with regard to menopausal status, history of pregnancy and abortion, coexisting benign uterine lesions, etc.), tumor markers (CEA, CA125, CA199), HPV-infection(HPVI), treatment regimens (surgery, radiotherapy and chemotherapy), and pathological results (specific pathological subtype, maximum lesion diameter, degree of tumor differentiation, International Federation of Gynecology and Obstetrics [FIGO] stage) between the two groups. All patients were followed up until July 30, 2023 and differences in therapeutic efficacy (complete response, stable disease, progressive disease) and survival outcomes (progression-free survival [PFS] and overall survival [OS]) were compared between the two patient groups following treatment.ResultsThe proportions of patients in the HPV-Ind-CA and HPV-CA groups were 14.2% and 85.8%, respectively. Most patients presented with irregular vaginal bleeding, and a significant number experienced contact bleeding. The patients in the HPV-Ind-CA group were older (≥50 years), had a lower degree of differentiation, a later FIGO stage (> I stage), higher CA125 levels, and constituted a greater number of postmenopausal patients (P < 0.05) than those in the HPV-CA group. The median PFS and OS in the HPV-Ind-CA group were 12 ± 25.5 and 21 ± 25.1 months, respectively; the 3-year OS and PFS rates were 70.21%, and 59.57%, respectively. In contrast, the median PFS in the HPV-CA group was significantly longer at 26 ± 32.3 months, with a corresponding median OS of 35 ± 31.9 months; their respective 3-year OS and PFS rates were 80.70% and 73.68%. The HPV-Ind-CA group demonstrated significantly shorter PFS and OS than the HPV-CA group (P < 0.05). In the HPV-Ind-CA cohort, low cervical adenocarcinoma differentiation (HR=152.673, 95% CI: 1.777–13117.314, P=0.027) and high CA199 levels (HR=104.888, 95%CI: 2.420–4546.373, P=0.016) were independent prognostic factors for OS. Conversely, in the HPV-CA cohort, the FIGO stage (> stage I), absence of HPVI, and high CA125 levels were independent prognostic factors influencing both OS and PFS outcomes; additionally, older age ≥ 50 years and high CA199 levels were independent risk factors for OS and PFS, respectively. Thus, greater than stage I FIGO stage and high CA125 and CA199 levels were identified as independent prognostic factors for PFS and OS in cervical adenocarcinoma. Furthermore, the absence of HPVI and older age of ≥50 years also constituted as independent risk factors for OS in this patient population.ConclusionsCompared with HPV-CA, HPV-Ind-CA is associated with inferior clinicopathological characteristics and survival outcomes. For patients who are HPV-negative and have elevated levels of CA125 and CA199, with a FIGO stage of I or higher, it is advisable to contemplate an intensified treatment protocol. This approach aims to enhance the opportunity for curative surgical resection when the patient’s physical condition permits it, thereby improving the overall prognosis.